Revitalizing the common peroneal function index for assessing functional recovery following nerve injury - Calder Fontaine; Eric A. Yeager; Michael Sledziona; Amanda K. Jones; Jonathan Cheetham (Brain and Behavior, 2021)
Abstract Background and Aims Peripheral nerve injury is common with poor functional recovery and consequent high personal and societal costs. Sciatic nerve transection and assessment of recovery using sciatic functional index (SFI) are widely used. SFI is biologically limited as axonal misdirection of axons supplying flexors and extensors in the hindlimb, after nerve injury can lead to synkinetic innervation and function which does not correspond to the degree of axonal regeneration. Methods We reevaluated the use of traditional metrics such as print length (PL), toe spread (TS), and intermediate toe spread (ITS) as well as hock angle at mid‐swing as approaches for determining recovery. We used two alternative approaches in discrete cohorts of rats following common peroneal crush injury, transection with repair and critical gap, using transection with ligation as a negative control. We compared walking track analysis (print) with digital capture and kinematics. Results PL, TS, and ITS varied as expected after injury. The traditional functional index for common peroneal injury using inked prints failed to describe recovery and we derived new indices to describe recovery (all R2 > 0.88, p < .0001) although pre‐injury PFI was never attained by any of the models. Kinematic analysis identified hock angle at mid‐swing as a useful predictor of recovery (p < .0001). Interpretation Using complementary approaches.